Ultra low loss and dual polarized SPR-PCF sensor based on refractive index - Irawan, Dedi; Ramadhan, Khaikal; Saktioto, Saktioto; Fitmawati, Fitmawati; Hanto, Dwi; Widiyatmoko, Bambang; Marwin, Azwir; Azhar, Azhar (Bulletin of Electrical Engineering and Informatics, 2023)
In this paper presents a numerical simulation using the finite element method (FEM) to analyze the performance of a photonic crystal fiber (PCF) integrated with plasmonic material sensor components. The sensor comprises silica and Au layers with a thickness of 45 nm, arranged in a simple geometric structure. Our proposed sensor component exhibits ultra-low loss, distinguishing it from previous studies that have focused on wavelength-sensitive (WS) and amplitude-sensitive (AS) measurement techniques. The refractive index (RI) range of the sensor component spans from 1.32 to 1.38 RIU. The maximum WS and AS values achieved are 6,000 nm/RIU, -373.4 1/RIU (x-polarization), and -385.4 1/RIU (y-polarization), respectively. Moreover, we demonstrate an ultra-low loss of 0.00117 dB/cm (x-polarized) and 0.00307 dB/cm (ypolarized). In terms of sensor resolution, this design achieves a remarkable resolution of 1.6×10-7 RIU for both x-and y-polarized measurements